1976
DOI: 10.3109/00498257609151616
|View full text |Cite
|
Sign up to set email alerts
|

Development of Liver Microsomal Oxidations in the Chick

Abstract: 1. Liver microsomal preparations from chick embryos (1 day before hatching) and from 1-7 day old chicks were assayed for oxidative drug-metabolizing activity with aminopyrine, aniline and naphthalene as substrates. 2. Activities for all three substrates were highest in preparations from 1 day-old chicks. These were more than twice as active as the 7 day-old preparations and about three times as active as those from the embryos. 3. The increase in drug-metabolizing activities in newly-hatched chicks was the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…It was later reported that newly hatched chickens had 3-4 times the adult enzyme activity and that this remained high for several days before returning to adult levels (8). 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) was first shown to be a potent inducer of 8-aminolevulinic acid synthetase and aryl hydrocarbon hydroxylase (AHHase; designated elsewhere as AHH) activity in the 17-DI chicken embryo (9).…”
mentioning
confidence: 99%
“…It was later reported that newly hatched chickens had 3-4 times the adult enzyme activity and that this remained high for several days before returning to adult levels (8). 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) was first shown to be a potent inducer of 8-aminolevulinic acid synthetase and aryl hydrocarbon hydroxylase (AHHase; designated elsewhere as AHH) activity in the 17-DI chicken embryo (9).…”
mentioning
confidence: 99%
“…adult trout (Table 5-1). The ontogeny of BPM activity in brook trout resembles that seen in chicken, where bùbstantial monooxygenase activity is present before hatching, and within 1 day after hatching activity rises to about twice the adult level (Powis et al, 1976).…”
Section: Induction Of Bp Monooxygenase Activity In Brook Trout Embryomentioning
confidence: 93%
“…Another possibility is that changes in the functional association of cytochrome P-450 and its reductase are responsible for the increased BPM activity after hatching. As discussed in the introduction, in the livers of chickens there is about a 3-fold increase in certain microsomal monooxygenase activities within 24 hours of hatching, but little change in the content of cytochrome P-450 or the level of NADPH-cytochrome c reductase activity (Powis et al, 1976).…”
Section: Ontogeny Of Microsomal Enzyme Activitiesmentioning
confidence: 99%
See 2 more Smart Citations